Effect of butyrine glycerides on the performance metrics and egg quality in laying pullets - Dey, B; Goswami, PK; Roddur, QAH; Jahan, N; Koly, S; Asif, AR (Bangladesh Journal of Animal Science, 2024)
The chicken feed industry is very much interested in creating innovative solutions to address the issue of safer animal products due to the increasing customer demand and the prohibition on utilizing antibiotic growth boosters. Organic acids, especially butyric acid, when added to chicken diets, have several beneficial effects on health, productivity, and egg quality. These factors may lead to their substitution in animal production systems for antibiotics. The study was determined the effects of butyrine glycerides (BAG) supplementation on various aspects of egg production and egg quality in laying pullets. Three dietary treatments were randomly assigned to 48 NovoGen Brown laying pullets at 24 weeks of age. For eighteen weeks, the chickens were kept in a three-tiered pyramid-style cage. The chickens in the control group (T1) were fed a basal diet; in groups T2 and T3, the basal diet was supplemented with 0.033% and 0.066% butyrine glycerides, respectively. Throughout the 12 weeks trial, measurements were made of the quantity and weight of eggs laid, feed conversion, and egg quality. Dietary supplementation of butyrine glycerides contributed to a significantly (p<0.001) increased in the egg production, egg weight and egg mass in laying pullets. Similarly, egg quality parameters did not affect significantly except shell percentage, albumen index and Haugh unit at 28th weeks of supplementation. Taken altogether, it is said that BAG positively impacted the laying performances and egg quality of laying pullets. Bangladesh Journal of Animal Science 53 (2): 31-39, 2024